Initial Knowledge at Radiation Protection Courses from 2005-2013 (3): Tendencies and Conclusions - Haverkamp, U. F.; Pruemer, B. A.; Fahrmer, A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: The necessity of refresher courses is controversial and is frequently questioned. The present study examines whether the courses have a lasting effect and whether improvements are indicated.Materials and Methods: With the help of a questionnaire (9 questions) to be answered before the course, a self-assessment was performed and questions about the knowledge and structure of radiation protection were asked. 1361 participants were surveyed (55 % physicians, 31 % doctor’s assistants, 13 % technicians, 1 % medical physicists) in the period of 2005 – 2013 (3) and 39 courses were evaluated. The assessment entailed the comparison of 3 subgroups: 2005 – 2007, 2008 – 2010, 2011 – 2013.Results: The self-assessment is about 3.0 (1 – very good, 5 – very poor) with fluctuations regarding time course and occupation. For all questions, there was an increase in correct answers from the period 2005 – 2007 to the period 2008 – 2010 (+ 15 %), while the rate fell again for the period 2011 – 2013 (3) (– 8 %). The questions were answered significantly better for organization-related topics than knowledge-based topics. Overall 53 % of the answers were correct.Conclusion: This study shows an increase in knowledge since starting refresher courses. However, recently the effect has decreased again. In order to maintain the knowledge, the yearly instruction must be held on time, which according to participants’ statements actually occurs in only 60 % of cases.Key Points:Citation Format:
Keywords: EU directive 97/43; refresher course; follow-up test